An Analysis of Illocutionary Acts in Song Lyrics of Nirvana’s Come as You Are and You Know You’re Right - Muhamad Rifan (Fakultas Ilmu Budaya, 2025)
This study examines the illocutionary acts in the lyrics of Nirvana’s songs Come As You Are and You Know You’re Right, which focus on the songwriter's intentions and the functions of each speech act. Using Searle’s (1969) theory of illocutionary act types and Leech’s (1983) framework of illocutionary functions, the research identifies and classifies 31 lyric lines without repetition from these songs. The study adopts a qualitative approach to analyze how each line performs an act such as stating, inviting, expressing, or promising, and how it functions socially and emotionally through collaborative, conflictive, competitive, or convivial purposes. The results show that in Come As You Are, the most frequent directive acts are often used primarily to invite or suggest actions, while collaborative functions are aimed at mutual understanding. In contrast, You Know You’re Right features more representative and commissive acts, which describe inner thoughts and emotional withdrawal. The collaborative function is also the most common in this song, and conflictive functions are the second most dominant, which reflects Kurt Cobain’s personal struggles and emotional intensity. This research concludes that Nirvana’s lyrics are rich in pragmatic meaning and communicative function. By combining Searle’s and Leech’s theories, the study reveals how lyrics used language not only to express emotions but also to connect, reject, or reflect on social and personal experiences. The findings emphasize that song lyrics can be a powerful form of speech and help uncover the deeper meanings behind artistic expression.
Reupload file repositori 26 Mar 2026_Maya
Keywords: Illocutionary Acts